(untitled) (Isagoge - Journal of Humanities and Social Sciences, 2023)
This paper was written in the format of an essay based on the impressions, reflections and desires that emerge from the daily work as a teacher trainer. It is an attempt to organize daydreams that haunt the profession, whose objective is to participate in the qualification of teachers for basic education schools. Here, two didactic daydreams are shared: the replacement of the curriculum by a menu of topics and the objective of making me an expendable teacher throughout a discipline of the teacher training course. These daydreams aim at another education, decolonizing the traditional process of transmitting knowledge, which only serves to strengthen the status quo.